The Priceless Scientific Heritage of the Great Thinker and his Study - Oltmisheva Nasibakhon Gulomjonovna (Periodica Journal, 2023)
The article presents opinions on the degree of study of the rich scientific heritage of the outstanding scientist of the Middle Ages Ahmad Fergani. And also, it deals with the significance of studying them for the present.
Keywords: Ahmad Fergani; early Middle Ages; Eastern Renaissance